Stability analysis of time-fractional differential equations with initial data - Bouteraa, Noureddine; İnç, Mustafa; Akgül, Ali (John Wiley and Sons Ltd, 2022)
In this work, we investigate the stability of solution for a class of time-fractional differential equation with initial data by the help of a fractional Duhamel principle; we use it and the superposition principle to obtain the solution of our problem. We present some theoretical results by some scientific theorems and lemmas. © 2021 John Wiley & Sons, Ltd.
Keywords: Duhamel principle; existence; spatial differential equation; stability